A Case Series and Review of Febrile-Infection Related Epilepsy Syndrome (FIRES) - Tahnee Spoden; Alice Hoftman; Nanci Rascoff; Deborah McCurdy (Children)
Background: FIRES is a rare and catastrophic presentation of a de novo refractory status epilepticus (RSE) in healthy individuals following mild febrile illness. It carries a high burden of morbidity and an estimated mortality of 12% in children. In over half of patients, an underlying cause is not discovered (cryptogenic FIRES). The theory that post-infectious inflammation promotes aberrant neuronal excitation has led to the use of immunomodulatory therapies as treatment for FIRES. High-dose glucocorticoids and intravenous immunoglobulin (IVIG) are used as first-line therapies but are ineffective in most cases. A comprehensive initial evaluation is critical in directing second-line therapies; however, an autoimmune and inflammatory workup is seldom completed prior to treatment. Despite recent trends toward using cytokine-directed therapies, outcomes remain poor. Methods: This single-institution retrospective case series describes three cases of FIRES in similarly aged children. Each patient experienced super-refractory status epilepticus (SRSE) resistant to first-line systemic immunotherapy (SIT). The novel use of baricitinib, a non-selective JAK inhibitor, proved effective for one patient, while IL-1 and IL-6 inhibition were effective in the other two. All patients suffered moderate-to-severe neurologic and cognitive impairment at the time of discharge. Conclusions: FIRES is a poorly understood catastrophic presentation of refractory status epilepticus (RSE) requiring a multimodal approach to treatment. Cytokine profiling can be helpful in identifying cryptogenic cases from those with an underlying cause if conducted early in the clinical course. The early use of second-line immunomodulatory therapies may aid in decreasing neuroinflammation and improve outcomes.